Metropolitan home: american style - Landis, Dylan (Clarkson Potter/Publishers, 1999)
Or well over twenty-five years, Metropolitan Home magazine has celebrated--and reported on its pages--creative homeowners, artists, decorators, architects, knowing that sensitive home design takes more than just a good eye. It also requires a good inner ear, tuned to the landscape and to the true voice of the house. Listening to the urban beat, for example, designer Carl D'Aquino ran movie theater carpet, dancing with pattern, up a five-story stair in a New York townhouse. In Texas, architects Ted Flato and David Lake crafted a house from a vast metal toolshed, a typical outbuilding in those parts. And in Philadelphia, Glen Senk and Keith Johnson decorated largely with restraint, keeping their historic house unrenovated and pristine--though they weren't above aging an army green wall with a coat of black shoe polish. The thirty-nine houses presented here are packed with design lessons. Each is a mix of inspiration and evocation, imagination and expertise. And each is highly adaptable for houses and apartments in other parts of the country.